A Systematic Review of the Literature on Trauma and Refugees - Anitha , L. R. (International Journal of Psychosocial Rehabilitation, 2020)
Refugees and asylum seekers are highly susceptible to the impacts of discrimination, conflict and displacement-related traumatic events. Overall, communities who are taken as slaves report exposure to a large number of potentially traumatic, repeated and prolonged adverse events. Through definition, the persecution of refugees means such incidents are often interpersonal in nature. Potentially traumatic incidents that refugees and asylum seekers often encounter in their home countries include interpersonal violence, sexual violence, life- threatening accidents, witnessing the murder of loved ones, and torture. For many, displacement may entail many months or even years of travel, living in areas affected by war or residing in refugee camps. In this article, the emphasis will be on empirical refugee research, asylum-seeker mental health and Trauma and Refugee analysis. By incorporating these different theories, the author describes an integrated model to assist service providers in identifying the different trauma factors associated with refugees, as well as facilitating the development of effective service delivery mechanisms for that population.